Sterilization of air filters for high pre-vacuum autoclaves. Issue 3 (May 1963) - Fallon, R. J.
Abstract : Experiments are described with glass fibre filter paper and complete glass filters as fitted to high pre-vacuum autoclaves to determine whether organisms can grow or penetrate through the filters. A filter consisting of four layers of glass fibre paper fitted inside a sterilizer chamber for a year and used for 96 sterilization cycles was found to have retained its initial efficiency.